2015
DOI: 10.1038/srep10948
|View full text |Cite
|
Sign up to set email alerts
|

Subgingival microbiome in patients with healthy and ailing dental implants

Abstract: Dental implants are commonly used to replace missing teeth. However, the dysbiotic polymicrobial communities of peri-implant sites are responsible for peri-implant diseases, such as peri-implant mucositis and peri-implantitis. In this study, we analyzed the microbial characteristics of oral plaque from peri-implant pockets or sulci of healthy implants (n = 10), peri-implant mucositis (n = 8) and peri-implantitis (n = 6) sites using pyrosequencing of the 16S rRNA gene. An increase in microbial diversity was obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
163
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(183 citation statements)
references
References 47 publications
15
163
4
1
Order By: Relevance
“…Of these, 87 were excluded after review of the title or abstract, and 39 1,9,10,13,14,16‐19,23‐52 full‐text studies were reviewed. Ultimately, 26 studies 9,10,13,14,16‐19,27,36‐52 were included (Table 1), and 13 1,23‐30,32‐35 were excluded for different reasons (12 1,23‐30,33‐35 for not fulfilling the proposed inclusion criteria and one 32 due to its retrospective design). In total, 1,145 patients with 2,134 implants were assessed in the 26 cross‐sectional studies studies 7,9,10,13,14,16‐19,27,36‐46,48‐52 that were included in this review.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Of these, 87 were excluded after review of the title or abstract, and 39 1,9,10,13,14,16‐19,23‐52 full‐text studies were reviewed. Ultimately, 26 studies 9,10,13,14,16‐19,27,36‐52 were included (Table 1), and 13 1,23‐30,32‐35 were excluded for different reasons (12 1,23‐30,33‐35 for not fulfilling the proposed inclusion criteria and one 32 due to its retrospective design). In total, 1,145 patients with 2,134 implants were assessed in the 26 cross‐sectional studies studies 7,9,10,13,14,16‐19,27,36‐46,48‐52 that were included in this review.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 21 studies comparing microbial profiles of peri‐implantitis and healthy implants were evaluated using different microbiologic methods: two used methods of cultivation, 37,40 two conventional polymerase chain reaction (PCR), 38,43 three quantitative PCR, 16,17,50 one nested‐PCR, 14 eight DNA hybridization, 9,13,27,36,39,41,42,49 and five DNA sequencing methods 18,19,44,47,51 . The major periodontopathic microorganisms (red complex: Porphyromonas gingivalis [ Pg ], Tannerella forsythia [ Tf ], and Treponema denticola [ Td ]; orange complex: Prevotella intermedia [ Pi ] and Fusobacterium nucleatum [ Fn ]; and other microorganisms: Aggregatibacter actinomycetemcomitans [ Aa ], Eikenella corrodens [ Ec ], Parvimonas micra [ Pm ], and Campylobacter rectus [ Cr ]) were identified in 11 of 21 studies (52.3%) 9,14,16,17,37,39,40,43,49,50,52 .…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the oral microbiota is also known to change in response to local and general conditions, and is considered to be an indicator of homeostatic deterioration (7,16,17). Although the association between oral and intestinal microbiota is unclear, recent studies have suggested that alterations in the microbial composition of dental plaque are associated with periodontal disease (6,18). In addition, a number of reports have suggested that periodontitis is linked to some systemic disorders, including diabetes mellitus (19,20).…”
Section: Originalmentioning
confidence: 99%
“…On the other hand, many identified bacteria such as Streptococcus sanguinis , Actinomyces naeslundii , Campylobacter rectus , Parvimonas micra , and Granulicatella adiacens or the genera Fusobacterium , Actinomyces , Veillonella , Atopobium , Gemella , Rothia , and Leptotrichia have been associated with healthy implants in previous studies 8,28‐30 . Special consideration should be taken with the genera Actinomyces and Veillonella as most authors 28,31 agreed to finding them more frequently in healthy implants, and none of the revised studies associate them with peri‐implantitis 8,28‐33 . Presence of these bacteria, together with Streptococcus mitis and S. sanguinis , may play a protective role regarding peri‐implant diseases 34,35 …”
Section: Discussionmentioning
confidence: 94%
“…A number of methods have been used to study the microbiota surrounding dental implants 6‐8 . Samples have been collected by rubbing or scratching implants with sterile paper points, curets, or periodontal probes.…”
mentioning
confidence: 99%